Effect of inhaler design variables on paediatric use of dry powder inhalers. - Anne J Lexmond; Tonnis J Kruizinga; Paul Hagedoorn; Bart L Rottier; Henderik W Frijlink; Anne H de Boer (PLoS ONE, 2014)
Age appropriateness is a major concern of pulmonary delivery devices, in particular of dry powder inhalers (DPIs), since their performance strongly depends on the inspiratory flow manoeuvre of the patient. Previous research on the use of DPIs by children focused mostly on specific DPIs or single inspiratory parameters. In this study, we investigated the requirements for a paediatric DPI more broadly using an instrumented test inhaler. Our primary aim was to assess the impact of airflow resistance on children's inspiratory flow profiles. Additionally, we investigated children's preferences for airflow resistance and mouthpiece design and how these relate to what may be most suitable for them. We tested 98 children (aged 4.7-12.6 years), of whom 91 were able to perform one or more correct inhalations through the test inhaler. We recorded flow profiles at five airflow resistances ranging from 0.025 to 0.055 kPa0.5.min.L-1 and computed various inspiratory flow parameters from these recordings. A sinuscope was used to observe any obstructions in the oral cavity during inhalation. 256 flow profiles were included for analysis. We found that both airflow resistance and the children's characteristics affect the inspiratory parameters. Our data suggest that a medium-high resistance is both suitable for and well appreciated by children aged 5-12 years. High incidences (up to 90%) of obstructions were found, which may restrict the use of DPIs by children. However, an oblong mouthpiece that was preferred the most appeared to positively affect the passageway through the oral cavity. To accommodate children from the age of 5 years onwards, a DPI should deliver a sufficiently high fine particle dose within an inhaled volume of 0.5 L and at a peak inspiratory flow rate of 25-40 L.min-1. We recommend taking these requirements into account for future paediatric inhaler development.